Kegiatan Pengabdian Di Desa Manurung Kalimantan Selatan Sebagai Desa Tenun dan Hilirisasi Produknya [Community Service Activities in Manurung Village, South Kalimantan, as a Weaving Village and Its Product Downstreaming] - Hadi, Samsul; Setiawan, Deni; Sukmana, M. Laily Qadry; Yusri, Yusri; Febriani, Noor Rahmi; Khadijah, Nor; Ulfah, Nahdiati; Indriani, Erika; Rahmawati, Nanda Hesti; Jannah, Fathul (Indonesia Berdaya, 2025)
Abstract. This community service activity was conducted in Manurung Village, Kusan Tengah District, Tanah Bumbu Regency, South Kalimantan, known as a traditional weaving village. The main challenges faced by the community are limited skills in producing value-added derivative products and a lack of understanding of Intellectual Property Rights (IPR). The objective of this activity was to improve sewing skills for woven-based products, strengthen innovative designs with an IPR orientation, and encourage downstream product processing to increase economic value. The activity employed a participatory approach through training, mentoring, and evaluation involving two partner groups: the Mandiri Weaving Group and the Pagatan Weaving Generation Group. The results of the activity showed a significant increase in assets, skills, and income. The Mandiri Weaving Group recorded a 250% increase in sewing skills and a 97.1% increase in income, while the Pagatan Weaving Generation Group experienced a 62.6% increase in assets and a 132% increase in income. Other visible impacts included increased motivation, cross-generational involvement, and awareness of the importance of IPR protection. In conclusion, this community service activity successfully strengthened Manurung Village's position as a weaving village by combining cultural preservation and sustainable creative economic development. Abstrak. Kegiatan pengabdian ini dilaksanakan di Desa Manurung, Kecamatan Kusan Tengah, Kabupaten Tanah Bumbu, Kalimantan Selatan, yang dikenal sebagai desa penghasil tenun tradisional. Permasalahan utama yang dihadapi masyarakat adalah keterbatasan keterampilan dalam menghasilkan produk turunan bernilai tambah serta minimnya pemahaman terkait Hak Kekayaan Intelektual (HKI). Tujuan dari kegiatan ini adalah meningkatkan keterampilan menjahit produk berbasis tenun, memperkuat desain inovatif dengan orientasi HKI, serta mendorong hilirisasi produk untuk memperbesar nilai ekonomi. Metode kegiatan menggunakan pendekatan partisipatif melalui pelatihan, pendampingan, dan evaluasi yang melibatkan dua kelompok mitra, yakni Kelompok Tenun Mandiri dan Kelompok Generasi Tenun Pagatan. Hasil kegiatan menunjukkan peningkatan aset, keterampilan, dan pendapatan secara signifikan. Kelompok Tenun Mandiri mencatat peningkatan keterampilan menjahit hingga 250% dan pendapatan 97,1%, sedangkan Kelompok Generasi Tenun Pagatan mengalami kenaikan aset sebesar 62,6% dan pendapatan hingga 132%. Dampak lain yang terlihat adalah meningkatnya motivasi, keterlibatan lintas generasi, serta kesadaran akan pentingnya perlindungan HKI. Kesimpulannya, kegiatan pengabdian ini berhasil memperkuat posisi Desa Manurung sebagai desa tenun dengan menggabungkan aspek pelestarian budaya dan pengembangan ekonomi kreatif yang berkelanjutan.